The association of pet ownership and sleep quality and sleep disorders in United States adults - Kayla Medlin; Lauren Wisnieski (Human-Animal Interactions, 2023)
Abstract Prior studies on the association between pet ownership and sleep quality and sleep disorders have varied results. Pet ownership may be beneficial for an owner’s quality of sleep due to the social support that pets provide. Pets offer a sense of security and companionship, which may result in improvements in levels of anxiety, stress, and depression. Alternatively, pets may disrupt their owners’ sleep. Therefore, this cross-sectional study aimed to determine if there is an association between dog and cat ownership and sleep quality and sleep disorders using data from the National Health and Nutrition Examination Survey (NHANES) conducted in 2005–2006. Separate multivariable logistic regression models were built to assess the association between pet ownership and sleep quality outcomes, which included the following: snoring, snorting, sleep disorder diagnoses, trouble sleeping, trouble falling asleep, waking up during the night, waking up too early, feeling unrested, feeling sleepy, not getting enough sleep, needing pills to sleep, leg jerks and cramps, taking longer than 15 minutes to fall asleep, and getting less than 6 hours of sleep on average. Demographics and body mass index (BMI) were adjusted in a series of hierarchical logistic regression analyses. Our results indicated that having a dog was associated with greater odds of having a sleep disorder and having trouble sleeping. Having a cat was associated with greater odds of having leg jerks. While the causal nature of pet ownership on sleep quality and sleep disorders was unable to be established, the results of this study are consistent with previous studies that found that pet ownership has a negative impact on sleep quality. The results of this study can inform randomized controlled trials for patients with poor sleep quality.